2022
DOI: 10.1088/1361-6463/ac5c1b
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence and EBIC investigations of stacking fault expansion in 4H-SiC due to e-beam irradiation at fixed points

Abstract: The effect of e-beam irradiation in the local and scan modes on the stacking fault expansion in 4H-SiC has been studied. It is shown that the distance, at which the e-beam affects the glide of partial dislocations driving the stacking fault expansion, does not exceed 10-12 μm. The dislocations were found to glide as straight lines with a velocity independent of their length, even when this length essentially exceeds the size of excitation volume. The irradiation at fixed points allows to separate the excess ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…[15,40] First of all, it is obtained that PDs move only if the beam is located at distances smaller than 10-12 μm independent of beam position inside or outside the SSFs that well correlates with the results reported previously for room temperature measurements. [15,40] This value is a little larger than the diffusion length and the size of excitation volume (about 3 μm at 20 keV) but the reason for this is not totally clear up to now. In any case, it can be stated that a focused e-beam enhances the Si-core PD mobility in a region with a size of about 20-25 μm.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…[15,40] First of all, it is obtained that PDs move only if the beam is located at distances smaller than 10-12 μm independent of beam position inside or outside the SSFs that well correlates with the results reported previously for room temperature measurements. [15,40] This value is a little larger than the diffusion length and the size of excitation volume (about 3 μm at 20 keV) but the reason for this is not totally clear up to now. In any case, it can be stated that a focused e-beam enhances the Si-core PD mobility in a region with a size of about 20-25 μm.…”
Section: Resultssupporting
confidence: 87%
“…To obtain the direct proof of such assumption LEEBI at fixed points is used as in. [15,40] First of all, it is obtained that PDs move only if the beam is located at distances smaller than 10-12 μm independent of beam position inside or outside the SSFs that well correlates with the results reported previously for room temperature measurements. [15,40] This value is a little larger than the diffusion length and the size of excitation volume (about 3 μm at 20 keV) but the reason for this is not totally clear up to now.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As shown in [ 38 ], some dislocations can move under electron beam excitation even at liquid nitrogen temperature, which means that, in such conditions, the activation energy for dislocation glide is close to 0. It is similar to REDG in 4H-SiC, for which it was shown that the low activation energy for REDG is determined by the very low activation energy for kink migration along partial dislocations [ 56 , 57 ]. It should be noted that, contrary to the case of 4H-SiC, in all measurements of REDG in GaN, only a small number of dislocations became mobile, which allows one to assume that dislocation pinning on obstacles essentially affects the dislocation motion.…”
Section: Introductionmentioning
confidence: 81%
“…However, even irradiation with the subthreshold energies can affect the electrical and optical properties of many semiconductor materials and structures (see, e.g., references in [96]). Thus, it is known that low energy electron beam irradiation (LEEBI) with beam energy of about 10 keV enhanced partial dislocation glide in 4H-SiC even at liquid nitrogen temperature [97][98][99][100][101][102][103] and dislocation glide in GaN [104][105][106]. As an example of point defect reconstruction under 63 Ni source with the activity of 2.7 mCi.…”
Section: Prediction Of Radiation Damagementioning
confidence: 99%